BATAS ANTARA RISIKO BISNIS DAN TINDAK PIDANA KORUPSI DALAM NEGARA HUKUM: STUDI KASUS INVESTASI TANIHUB OLEH NICKO WIDJAJA - Luvina Dien Auliya; Nadilla Asma Dzakiyah; Keisha Riyana; Ega Yonsu Al-Fauziah; Nadiya Indahnya Rahmadani; Suryo Ediyono (CV. Denasya Smart Publisher, 2026)
The Nicko Widjaja case has sparked debate regarding the concept of the rule of law, particularly concerning the line between business risk and criminal acts of corruption. The case originated from a failed investment by BRI Ventures in the startup TaniHub, which led to Nicko Widjaja being charged as a suspect in a case involving alleged losses to the state, with the prosecution demanding an 11 year prison sentence and a fine of 1 billion rupiah. This raises the question of whether every business failure that causes state losses. It constitutes an unlawful act. This study aims to analyze the boundary between business risks which are a normal part of business practice and legal certainty within a rule of law state. This study is essential to prevent the criminalization of business decisions made in good faith. The approach used is a juridical-normative one, which examines the principles of the business judgment rule, legal certainty, and the principle of legality. The results of the study indicate that not all business losses are subject to criminal penalties; rather, such penalties must be supported by evidence of abuse of authority, conflicts of interest, and malicious intent. Careless law enforcement has the potential to undermine legal certainty. Therefore, it is necessary to clarify the boundaries between the business and criminal domains in order to strike a balance between legal certainty for business owners and the protection of state finances.